2015
DOI: 10.7727/wimjopen.2014.003
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Cognitive Impairment among Older Adults in Jamaica

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 41 publications
3
14
0
1
Order By: Relevance
“…This finding is in agreement with other studies. 20,35,49,51,52,56,58 This might be due to decline in gray matter volume, neurotransmitter, and neocortical synapses during aging which result in cognitive impairment. [59][60][61]…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with other studies. 20,35,49,51,52,56,58 This might be due to decline in gray matter volume, neurotransmitter, and neocortical synapses during aging which result in cognitive impairment. [59][60][61]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, aging populations are also shown to be associated with increased odds of cognitive impairment over time . Decline in cognitive performance may increase the risk and fear of falling, dependence in activities of daily living, and decline in thinking skills …”
Section: Introductionmentioning
confidence: 99%
“…10 Decline in cognitive performance may increase the risk and fear of falling, dependence in activities of daily living, and decline in thinking skills. 11 Depression, loneliness, reduced cognitive function and quality of life, and sensory impairment are common in older adults. Thus, understanding the association of sensory impairment and depression, loneliness, cognitive function, and quality of life is important.…”
Section: Introductionmentioning
confidence: 99%
“…showed that 42.9% of the elderly had CI[ 20 ] and in another study among the inmates of old age home in Hyderabad, it was found to be 38%. [ 21 ] The prevalence of CI among community-dwelling older adults in Jamaica was found to be 32.2%,[ 22 ] whereas, in a study conducted in elderly care home in Malaysia, it was found to be 36.5%. [ 23 ] All these were more or less similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] The study in Shimla hills showed that increasing age, educational level, and marital status acting as significant predictors of CI in the elderly. [ 22 ] Ferdous et al . in a study done in 457 elderly subjects in rural Bangladesh, found that poorer cognitive performance was independently associated with older age, female sex, and illiteracy.…”
Section: Discussionmentioning
confidence: 99%